Fenotipagem de porta-enxertos de pessegueiros para reação à Meloidogyne incognita (Kofoid e White) Chitwood (1949) e estudo da variabilidade genética com marcadores de microssatélites - Paula, Luciane Arantes de (2009)
The Rio Grande do Sul state (RS) represents great importance in the stone fruit, with approximately 65% of the area cultivated with peach country. This should highlight the contribution of the breeding of new cultivars crown, which extend the period allowed for collection and quality of fruit. Still, the average productivity in the RS is still considered low, mainly due to lack of knowledge about factors related to incidence of pests, diseases and lack of root stock suitable for cultivation, because unlike other countries, the improvement in Brazil genetic of the rootstocks for stone fruit of importance has taken only a few years ago. This thesis is divided into three chapters, with chapter 1 was to evaluate the reaction of five peach rootstocks, from front to inoculation with Meloidogyne incognita, in a home-de-vegetation. And we can conclude that 'Selection UFPel-0402', 'Okinawa', 'Flordaguard', Nagano Wild‟ and 'Select NR-0080407' are immune to Meloidogyne incognita, and may be used in genetic improvement programs for the rootstocks of peach and as alternative use for the deployment of orchards in areas with occurrence of the pest, and the strength of the 'Nagano Wild' needs further studies to identify more clearly this characteristic. Chapter 2 objective evaluated the genetic variability and differentiation of 14 rootstocks, peach, setting a standard for molecular characterization of each genotype, based on loci of SSR, SCAR and STS, for future work on genetic improvement and it is concluded that markers of microsatellites can be relatively easily a pattern of molecular genotypes of the rootstocks of peach and solve problem of homonymy, the example of the evaluated genotypes of Okinawa, and shows which are more contrasting genotypes for use in breeding. Chapter 3 objective to estimate frequencies of recombination among molecular markers, and the color of leaf, from the analysis of a F2 segregating population ('Capdeboscq' x 'Flordaguard'), and check if the connection is similar to that obtained in other mapping populations. It can be concluded that based on molecular maps for Prunus spp. available in the literature and from results obtained in this work, it was concluded that the markers UDP96-013 and BPPCT-034 are linked in different mapping populations, and potential candidates for use in the selection of new resistant genotypes to Meloidogyne spp. .